Biflanged metal stents versus plastic stents for endoscopic ultrasound-guided drainage of walled-off necrosis: a randomized controlled trial - Koduri, Krithi Krishna; Jagtap, Nitin; Lakhtakia, Sundeep; Jahangeer, Basha; Asif, Shujaath; Talukdar, Rupjyoti; Trikudanathan, Guru; Tandan, Manu; Kalapala, Rakesh; Nabi, Zaheer; Gupta, Rajesh; Ramchandani, Mohan; Singh, Jagadish; Memon, Sana Fatima; Rao, G. Venkat; Reddy, D. Nageshwar (Endoscopy, 2024)
Background Endoscopic ultrasound (EUS)-guided drainage of walled-off necrosis (WON) using either plastic or metal stents is the mainstay of WON management. Our single-center randomized controlled trial aimed to evaluate the efficacy of biflanged metal stents (BFMSs) and plastic stents for WON drainage.Methods Patients with symptomatic WON amenable to EUS-guided drainage were randomized to receive either BFMSs or plastic stents. The primary outcome was reintervention-free clinical success at 4 weeks. Secondary outcomes were: overall clinical success (complete resolution of symptoms and significant reduction in size of WON [<50% of original size and <5 cm in largest diameter at 4-week follow-up]); number of reinterventions; adverse events (AEs); hospital stay for first admission; and medium-term outcomes at 6 months (recurrence, disconnected pancreatic duct, chronic pancreatitis, and new-onset diabetes mellitus).Results 92 patients were randomized: 46 in each arm. The reintervention-free clinical success rate was significantly higher in the BFMS group on intention-to-treat analysis (67.4% vs. 43.5%; P = 0.02). Overall clinical success at 1 month was similar in both groups. There were significantly fewer reinterventions (median 0 [IQR 0–1] vs. 1 [0–2]; P = 0.03) and shorter hospital stays in the BFMS group (7.0 [SD 3.4] vs. 9.1 [5.5] days; P = 0.04). There were no differences in procedure-related AEs, mortality, or medium-term outcomes.Conclusions BFMSs provide better reintervention-free clinical success at 4 weeks, with shorter hospital stay and without increased risks of AEs, compared with plastic stents for EUS-guided drainage of WON. Medium-term outcomes are however similar for both stent types.